Figeno: multi-region genomic figures with long-read support - Sollier, Etienne; Heilmann, Jessica; Gerhäuser, Clarissa; Scherer, Michael; Plass, Christoph; Lutsik, Pavlo (Bioinformatics, 2024)
The vast amount of publicly available genomic data requires analysis and visualization tools. Here, we present figeno, an application for generating publication-quality FIgures for GENOmics. Figeno particularly focuses on multi-region views across genomic breakpoints and on long reads with base modifications. In addition, we support epigenomic data including ATAC-seq, ChIP-seq or HiC, as well as whole genome sequencing data with copy numbers and structural variants.Figeno is available as a python package with both a command line and graphical user interface. It can be installed via PyPI and the source code is available at https://github.com/CompEpigen/figeno.
Veröffentlicht: 10. Juni 2024
Gesehen am 21.11.2024